Long-term topical corticosteroid use and risk of skin cancer: a systematic review protocol - Ratib, Sonia; Burden-Teh, Esther; Leonardi-Bee, Jo; Harwood, Catherine; Bath-Hextall, Fiona (Wolters Kluwer Health, 2016)
Review question/objective: The objective of this systematic review is to synthesize the best available research evidence to determine the risk of skin cancer in patients on long-term use of topical corticosteroids. Specifically the review question is: In people using long-term (regular use over one month) topical corticosteroids, what is the risk of developing skin cancer (clinically or histologically confirmed basal cell carcinoma, squamous cell carcinoma or melanoma)?